In vitro anticancer, antimicrobial and antifungal activity analysis of natural flavonoid hesperidin - Çerçi Öngün, Berfu; Mutlu Altundağ, Ergül; Altınoğlu, Gülcem; Güran, Mümtaz; Şanlıtürk, Gizem; Afshani, Masoud; Balcı, Deniz (Progress in Nutrition, 2022)
Hesperidin, a plant flavonoid mainly found in citrus fruits, has been shown to have important biological activities, while its effects on GBM cells and against pathogen microorganisms are largely unknown.  In this study, the cell viability effect of hesperidin on human GBM cells and the antibacterial and antifungal properties against a comprehensive set of microorganisms in vitro were explored. To assess the anti-proliferative effect of hesperidin on human GBM cells at different time points, GBM cells were treated with hesperidin at different concentrations. Cell viability was evaluated by MTT assay and cell nuclear morphology of hesperidin treated GBM cells was studied using DAPI staining. Hesperidin’s antimicrobial activity was screened with standard broth microdilution assays for antibacterial and antifungal activity screening. Antibacterial activity further tested by Antibacterial well diffusion assay. Hesperidin treatment significantly inhibited the cell viability in a concentration and time dependent manner, where the point of decrease in cell viability has been found at 150 and 200 μM of hesperidin treatment for 48 and 72 h. DAPI staining showed the induction of apoptosis in GBM cells following hesperidin treatment for 72 h at increased concentrations. The antimicrobial activity tests for hesperidin revealed no significant antimicrobial activity including antibacterial and antifungal assays. It can be concluded that hesperidin possesses anti-cancer properties in GBM cells in vitro resulting in reduced cell viability, proliferation and increased apoptosis, and may be effective against brain gliomas, with no significant antimicrobial activity.